Typological Analysis of Gedung Kesenian Jakarta: Preserving Colonial Legacy and Local Identity - Nidauljannah, Karina; Pramantha, Raudina Qisthi (Universitas Syiah Kuala, 2024)
This research examines the architectural typology of Gedung Kesenian Jakarta (GKJ), or Jakarta Arts Building, which stands as a significant remnant of classical Dutch colonial architecture. The study aims to identify the characteristics of the building's architectural design and investigate changes in the function of spaces and building elements before and after the 1987 renovation. Using a descriptive qualitative approach, the research employs a combination of data collection techniques, including observation, interviews, documentation, and literature review. The observation criteria focus on the buildings elements and their composition in relation to its function as the theatre of art performances. The findings indicate that the authenticity of Gedung Kesenian Jakarta has been largely preserved. However, the research identifies several differences between the pre-and post-restoration periods. Notable changes include the addition of new spaces and the reconstruction of certain building elements. Despite these alterations, the additions respect the original architectural form and character, maintaining the buildings historical integrity while maximizing the needs of theatre activities and accommodating the significance of the local ornaments. Overall, this study highlights the ongoing relevance of GKJ as both an architectural and cultural heritage site, reflecting Jakartas role in the development of art and architecture since the Dutch colonial era.Keywords: Art Building, Classical Architecture, Typology, Colonial